Investigation of Factors Affecting the Sense of Community of Distance Education Learners in Online Learning Environments - Esma Yıldız (Anı Publishing, 2020)
The purpose of this study is to determine the factors that influence the sense of community of learners in online learning environments. Participants of the study consisted of 15 students from 5 different departments in Distance Learning Application and Research Center (UZEM). The study was conducted through semi-structured interviews with qualitative data collection tools. The data obtained through interviews with participants were analyzed by content analysis with a computer program. After the analysis of the data, seven themes that influence the sense of community of learners in online learning environments were defined. These themes are (1) instructor, (2) learners characteristics, (3) instructional design, (4) teaching method, (5) interaction, (6) collaboration and (7) orientation. While organizing online learning environments, it is emphasized that instructors should be informed about the process, interaction interfaces should be designed, system orientations should be made, and appropriate methods and strategies should be determined.